An atomistic study of the structural changes in a Zr–Cu–Ni–Al glass-forming liquid on vitrification monitored in-situ by X-ray diffraction and molecular dynamics simulation - Louzguine-Luzgin, Dmitri V.; Georgarakis, Konstantinos; Andrieux, Jérôme; Hennet, Louis; Morishita, T.; Nishio, K.; Belosludov, R. V. (Elsevier, 2020)
Structural changes in the Zr55Cu30Ni5Al10 liquid alloy on cooling from above the equilibrium liquidus temperature are studied by synchrotron radiation X-ray diffraction and compared with the results of first-principles molecular dynamics simulation. In-situ vitrification of the studied alloy is achieved using a containerless levitation technique. Subsequent analysis of the atomic and electronic structure of the alloy in liquid and glassy states reveals formation of medium-range order on cooling and its relationship with liquid fragility. The structural changes in this alloy are smaller in comparison with a more fragile one.
Keywords: Metallic glass; Liquid; Fragility; X-ray diffraction; Structure; Synchrotron radiation